Consumer Environmental Awareness, Attitude and Behavior: Case Study of a Higher Education Institution - Bastaman, Aam (Journal of Entrepreneurship, Business and Economics, 2020)
Consumers play a pivotal role in the efficiency program of energy which supports the environmental friendly consumption for environmental sustainability. The energy generation depends on non-renewable resources to a great extent which are originated from fossil, such as coal, oil and gas. The fact is that the fossil resource so limited which is predicted will be last in the near decade. The usage of fossil energy is also blamed as the cause of global warming and climate change. The changing in consumer consumption behavior is important to solve or at least to ease the challenge of the scarcity of fossil energy. Now we can see the growing interest to the environmental protection which led to the emergence of new environmental paradigm (NEP). This research will test using the new environmental paradigm scale to predict the consumer awareness, afterwards to test the degree of relationship between environmental awareness to the environmental concerns, then to test the influence of environmental awareness to the attitude of energy saving consumption, and finally to test consumer attitude of energy saving consumption to the behavior of energy consumption. Respondents are well educated consumers with minimum undergraduate degree holder. This research finds that the degree consumer environmental concern based on NEP scale is moderate. In the meantime, there is no strong relationship between environmental awareness and environmental concerns. Consumer’s environmental concern has no influence towards attitude of energy saving. However, attitude of energy saving influenced the energy consumption behavior. Research paper Keywords: Environmental awareness; environmental concern; new environmental paradigm; attitude; behavior Reference to this paper should be made as follows: Bastaman, A. (2020). Consumer Environmental Awareness, Attitude and Behavior: Case Study of a Higher Education Institution, Journal of Entrepreneurship, Business and Economics , 8 (1), 121–143.